Colitogenic effector T cells: roles of gut‐homing integrin, gut antigen specificity and γδ T cells. Issue 1 (5th November 2013) - Do, Jeong‐su; Visperas, Anabelle; Freeman, Michael L; Iwakura, Yoichiro; Oukka, Mohamed; Min, Booki
Abstract : Disturbance of T‐cell homeostasis could lead to intestinal inflammation. Naive CD4 T cells undergoing spontaneous proliferation, a robust proliferative response that occurs under severe lymphopenic conditions, differentiate into effector cells producing Th1‐ and/or Th17‐type cytokines and induce a chronic inflammation in the intestine that resembles human inflammatory bowel disease. In this study, we investigated the key properties of CD4 T cells necessary to induce experimental colitis. α4β7 upregulation was primarily induced by mesenteric lymph node (mLN) resident CD11b + dendritic cell subsets via transforming growth factor beta (TGFβ)/retinoic acid‐dependent mechanism. Interestingly, α4β7 expression was essential but not sufficient to induce inflammation. In addition to gut‐homing specificity, expression of gut Ag specificity was also crucial. T‐cell acquisition of the specificity was dramatically enhanced by the presence of γδ T cells, a population previously shown to exacerbate T‐cell‐mediated colitis. Importantly, interleukin (IL)‐23‐mediated γδ T cell stimulation was necessary to enhance colitogenicity but not gut antigen reactivity of proliferating CD4 T cells. These findings demonstrate that T‐cell colitogenicity is achieved through multiple processes, offering a therapeutic rationale by intervening these pathways.